2018
DOI: 10.1038/s41598-018-35545-7
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana DGAT3 is a [2Fe-2S] protein involved in TAG biosynthesis

Abstract: Acyl-CoA:diacylglycerol acyltransferases 3 (DGAT3) are described as plant cytosolic enzymes synthesizing triacylglycerol. Their protein sequences exhibit a thioredoxin-like ferredoxin domain typical of a class of ferredoxins harboring a [2Fe-2S] cluster. The Arabidopsis thaliana DGAT3 (AtDGAT3; At1g48300) protein is detected in germinating seeds. The recombinant purified protein produced from Escherichia coli, although very unstable, exhibits DGAT activity in vitro. A shorter protein version devoid of its N-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 48 publications
(70 reference statements)
1
45
0
Order By: Relevance
“…Phylogenetic analyses indicated that P. lindheimeri DGATs were closely related to their lesquerella orthologs ( Figure 9 B,D,F) ( Figure 10 A–C), showing aa similarity at 84.3% with PfDGAT1-1, 84.9% with PfDGAT2, and 89.4% with PfDGAT3, respectively ( Supplementary File 6, Tables S13–S15 ). Among these three DGAT families, the role of DGAT3 in seed TAG synthesis has not yet been established [ 94 ], but it has been shown to be involved in recycling FAs in general lipid metabolism [ 94 , 95 , 96 ]. DGAT1 and DGAT2 have been intensively studied.…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic analyses indicated that P. lindheimeri DGATs were closely related to their lesquerella orthologs ( Figure 9 B,D,F) ( Figure 10 A–C), showing aa similarity at 84.3% with PfDGAT1-1, 84.9% with PfDGAT2, and 89.4% with PfDGAT3, respectively ( Supplementary File 6, Tables S13–S15 ). Among these three DGAT families, the role of DGAT3 in seed TAG synthesis has not yet been established [ 94 ], but it has been shown to be involved in recycling FAs in general lipid metabolism [ 94 , 95 , 96 ]. DGAT1 and DGAT2 have been intensively studied.…”
Section: Resultsmentioning
confidence: 99%
“…A third form of DGAT, DGAT3, has been identified in plants but is unlike the other known DGAT forms, soluble (Saha et al, 2006). While the DGAT activity of DGAT3 has been demonstrated in several studies (Saha et al, 2006; Hernández et al, 2012; Chi et al, 2014; Aymé et al, 2018), no clear evidence of its participation in seed oil accumulation has yet been presented.…”
Section: Introductionmentioning
confidence: 99%
“…DGATs are represented in plants by at least two enzymes, DGAT1 and DGAT2, which are only distantly related in an evolutionary sense (see Xu et al, 2018, for review). A third enzyme with DGAT activity, DGAT3, has also been identified, although its physiological role in TAG synthesis has not yet been established (Ayméet al, 2018). An Arabidopsis DGAT1 mutant has lower levels of seed oil and increased levels of polyunsaturated fatty acids (FAs) (Zou et al, 1999).…”
Section: Introductionmentioning
confidence: 99%